Pancreatic surgery outcomes: multicentre prospective snapshot study in 67 countries - Fusai, Giuseppe; Raptis, Dimitri A.; Ferrone, Cristina R.; Hidalgo Salinas, Camila; Hilal, Mohammed Abu; Bassi, Claudio; Besselink, Marc G.; Conlon, Kevin C.; Davidson, Brian R.; Del Chiaro, Marco; Dervenis, Christos; Falconi, Massimo; et al. (The British journal of surgery, 2024)
Pancreatic surgery remains associated with high morbidity rates. Although postoperative mortality appears to have improved with specialization, the outcomes reported in the literature reflect the activity of highly specialized centres. The aim of this study was to evaluate the outcomes following pancreatic surgery worldwide.This was an international, prospective, multicentre, cross-sectional snapshot study of consecutive patients undergoing pancreatic operations worldwide in a 3-month interval in 2021. The primary outcome was postoperative mortality within 90 days of surgery. Multivariable logistic regression was used to explore relationships with Human Development Index (HDI) and other parameters.A total of 4223 patients from 67 countries were analysed. A complication of any severity was detected in 68.7 per cent of patients (2901 of 4223). Major complication rates (Clavien-Dindo grade at least IIIa) were 24, 18, and 27 per cent, and mortality rates were 10, 5, and 5 per cent in low-to-middle-, high-, and very high-HDI countries respectively. The 90-day postoperative mortality rate was 5.4 per cent (229 of 4223) overall, but was significantly higher in the low-to-middle-HDI group (adjusted OR 2.88, 95 per cent c.i. 1.80 to 4.48). The overall failure-to-rescue rate was 21 per cent; however, it was 41 per cent in low-to-middle- compared with 19 per cent in very high-HDI countries.Excess mortality in low-to-middle-HDI countries could be attributable to failure to rescue of patients from severe complications. The authors call for a collaborative response from international and regional associations of pancreatic surgeons to address management related to death from postoperative complications to tackle the global disparities in the outcomes of pancreatic surgery (NCT04652271; ISRCTN95140761).Pancreatic surgery can sometimes lead to health problems afterwards. Although some top hospitals report good results, it is not clear how patients are doing all over the world. The aim was to find out how people are recovering after pancreatic surgery in different countries, and to see whether where they live affects their health outcomes after pancreatic surgery. The health records of 4223 patients from 67 countries who had pancreatic surgery in a 3-month interval in 2021 were studied, especially looking at how many people faced serious complications or passed away within 90 days of the surgery. Almost 7 in 10 patients faced some health problems after operation. The chance of having a major health issue or dying after the surgery was higher in countries with fewer resources and less developed healthcare. For example, 10 of 100 patients died after the surgery in these countries, but only 5 of 100 patients did in richer countries. What stands out is that countries with fewer resources have a tougher time getting patients back to health when things go wrong after surgery. It is hoped that doctors and medical groups worldwide can work together to improve these outcomes and give everyone the best chance of recovering well after pancreatic surgery.
Gesehen am 25.02.2025
Online veröffentlicht: 9. November 2023